2011
DOI: 10.1007/s10531-011-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Oil and gas development in the World Heritage and wider protected area network in sub-Saharan Africa

Abstract: More than 25% of natural World Heritage (WH) sites worldwide are estimated to be under pressure from existing or future mining and energy activities (IUCN 2008; UNESCO 2009). However, that 'pressure' has yet to be quantitatively defined and assessed for many regions of the world. We conducted a GIS-based analysis of overlap and proximity between natural WH sites and areas allocated to oil and gas concessions as well as pipelines and oil wells for all of sub-Saharan Africa. We found that oil and gas concession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
1
15
0
5
Order By: Relevance
“…In our study site as in other places (Osti et al 2011), poaching seems to be associated with urbanization and land conversion for agriculture. It is thus crucial that hydrocarbon companies engage in discussion with the surrounding municipalities and farmers to control urban and agriculture expansion inside their concession (Abernethy et al 2013).…”
Section: Control Of Urban and Agricultural Expansionsupporting
confidence: 54%
“…In our study site as in other places (Osti et al 2011), poaching seems to be associated with urbanization and land conversion for agriculture. It is thus crucial that hydrocarbon companies engage in discussion with the surrounding municipalities and farmers to control urban and agriculture expansion inside their concession (Abernethy et al 2013).…”
Section: Control Of Urban and Agricultural Expansionsupporting
confidence: 54%
“…The methodology employed herein is only one of the many options available to practitioners for the mapping and monitoring of oil exploration and oil exploitation activities in desert ecosystems. Other possible methods include the use of purely geographic information systems-based analyses, as employed by Osti et al [34]. However, this form of analysis relies heavily on global energy and environment data providers and consultancies, such as the information handling services, which is not free of charge and may potentially be less objective than the use of open access satellite imagery.…”
Section: Discussionmentioning
confidence: 99%
“…There has never been a survey of the number of companies operating in protected areas so it is impossible to say how common this is, although the trend seems to be for an increase. A study in Africa found 27 per cent of natural World Heritage sites had oil and gas concessions inside their borders although none were currently operational (Osti et al, 2011); an expected boom in African mining (Edwards et al, 2014) could rapidly change this. Together protected areas and indigenous territories put 49.9 per cent of the Amazon's total habitat under protection (Maretti et al, 2014).…”
Section: How Have Company Attitudes To No-go Changed Since 2000?mentioning
confidence: 99%